Respuesta :
Answer:
(3-x)/9
Step-by-step explanation:
(9-x^2)
---------------
9x+27
Factor the numerator and denominator
(3-x) (3+x)
----------------
9(x+3)
Rewriting the denominator as 3+x
(3-x) (3+x)
----------------
9(3+x)
Canceling 3+x from the numerator and denominator
(3-x)
----------------
9
ANSWER
[tex] \frac{3 - x}{9} [/tex]
EXPLANATION
The given expression is
[tex] \frac{9 - {x}^{2} }{9x + 27} [/tex]
We rewrite as a difference of two squares to get,
[tex] = \frac{ {3}^{2} - {x}^{2} }{9x + 27} [/tex]
Recall that,
[tex]a^2-b^2=(a - b)(a+ b)[/tex]
We factor to obtain,
[tex] = \frac{(3 - x)(3 + x)}{9(x + 3)} [/tex]
We now cancel out the common factors to get,
[tex] = \frac{3 - x}{9} [/tex]
[tex] \frac{3 - x}{9} [/tex]
EXPLANATION
The given expression is
[tex] \frac{9 - {x}^{2} }{9x + 27} [/tex]
We rewrite as a difference of two squares to get,
[tex] = \frac{ {3}^{2} - {x}^{2} }{9x + 27} [/tex]
Recall that,
[tex]a^2-b^2=(a - b)(a+ b)[/tex]
We factor to obtain,
[tex] = \frac{(3 - x)(3 + x)}{9(x + 3)} [/tex]
We now cancel out the common factors to get,
[tex] = \frac{3 - x}{9} [/tex]